EFEKTIVITAS PEMBELAJARAN POLA PENDIDIKAN SISTEM GANDA PADA SEKOLAH KEJURUAN DI KOTA PONTIANAK - Syarifah Novieyana; Evi Sofiana; Tri Wahyuarini (Inovbiz: Jurnal Inovasi Bisnis, 2018)
One of Indonesian Goverment policies in Educational sectors is to reinforce vocational education pattern policy named Vocational High School with Dual Responsibiluty System. Current research is learning effectiveness of Dual Resposbility Sustem at Vocational schools located in Pontianak, which aimed at investigates empirically all the variables affect Dual Responsiility System  partially and also to find out the determinate factors on Dual Responsibility System. Survey with questionnaire is deployed for data collecting with 135 respondents valid for further analyzed. Validity, reliabilty and classic assumption were used for measurement and Likert Scale for variable measurement as well. Data analysis and variable analyzes, current study highlights that teachers competency andlearning facility shows a significant impact on Dual Responsibility System. In another hands, the finding shows also showed that exogent variable has asignificant impact on endogen with R Square 52,6%,  0,430. This research suggests that each vocational schools to apply ARCS in motivating the students as well as the innovation, maintenance of learning facilities usage. Moreover, it’s also suggest that goverment especially Educational Department of Pontianak to evaluate the effectiveness of Dual Responsibilty System Implementation in Vocational High Schools in Pontianak.